Accuracy of NT-proBNP for predicting mortality amongst patients with ischemic stroke: a systematic review and meta-analysis - Jun Ran; Yun Liu; Hao Ma; Yu Zhang (BMC Medicine)
Background Ischemic stroke remains one of the leading causes of morbidity and mortality worldwide. NT-proBNP is emerging as a promising biomarker for risk stratification in acute ischemic stroke. This review aimed to assess its prognostic accuracy for mortality in this patient population. Methods We conducted a comprehensive literature search across databases (PubMed, Embase, Web of Science, Scopus and Cochrane Library), retrieving 4832 records. Following duplicate removal and full-text screening, 11 prospective observational studies meeting the inclusion criteria were included. Data on study characteristics, risk of bias, and diagnostic performance (sensitivity, specificity, likelihood ratios, diagnostic odds ratio, and area under the ROC curve [AUROC]) were extracted and pooled using a bivariate random-effects model. Results The 11 studies included 2994 patients (12.19% mortality). Pooled prognostic performance of NT‐proBNP for mortality showed a sensitivity of 0.83 (95% CI, 0.73–0.89) and specificity of 0.77 (95% CI, 0.67–0.84), with an area under the receiver operating characteristic curve (AUROC) of 0.87 (95% CI, 0.84–0.90). In subgroup analyses, NT‐proBNP demonstrated a sensitivity of 0.84 and specificity of 0.70 (AUROC = 0.86) for predicting in-hospital mortality (5 studies), and sensitivity of 0.81 and specificity of 0.87 (AUROC = 0.91) for predicting 3‐month mortality (4 studies). The positive likelihood ratio was 3.5, and the negative likelihood ratio was 0.23, corresponding to a diagnostic odds ratio of 16. Conclusions NT-proBNP demonstrates moderate to high accuracy for predicting mortality in acute ischemic stroke, supporting its potential role in clinical risk stratification. Further standardized, multicenter research is warranted to confirm optimal threshold values and to evaluate its impact on patient management.